Marginal Compensated Effects in Discrete Labor Supply Models - John K. Dagsvik; Steinar Strøm; Marilena Locatelli (Center for Economic Studies and ifo Institute (CESifo), 2019)
This paper develops analytic results for marginal compensated effects of discrete labor supply models, including Slutsky equations. It matters, when evaluating marginal compensated effects in discrete choice labor supply models, whether one considers wage increase (right marginal effects) or wage decrease (left marginal effects). We show how the results obtained can be used to calculate the marginal cost of public funds in the context of discrete labor supply models. Subsequently, we use the empirical labor supply model of Dagsvik and Strøm (2006) to compute numerical compensated (Hicksian) and uncompensated marginal (Marshallian) effects resulting from wage changes. The mean Hicksian labor supply elasticities are larger than the Marshallian, but the difference is small.
Keywords: J22; C51; 330; Slutsky equations; discrete choice labor supply